PENGARUH BOKASI TITONIA (Titonia diversifolia) TERHADAP.. ......SERAPAN K (KALIUM) DAN PRODUKSI BAWANG MERAH ,... (Alium ascallonicum L.) VARIETAS LEMBAH PALU PADA ENTISOL GUNTARANO - Dwiyulianto putra; Imam Wahyudi; Yosep Soge Pata’ dungan (Universitas Tadulako, 2013)
An experiment was conducted to determine the effect of Titonia bokashi on the changes in the level of potassium (K) up take and yield of shallot (Allium ascalonicum L.) grown on Entisol. The experiment was arranged in a Randomized Block Design (RBD) with the rates of bokashi includingno bokashi added (to), 10 t ha-1(t1), 20 t ha-1(t2), 30 t ha-1(t3), 40 t ha-1(t4), 50 t ha-1(t5), and 60 t ha-1(t6). Each treatment was replicated three times so that there were 21 experimental units. The application of Titonia bokashi up to 60 t ha-1was proven to effectively increase soil C-organic, K-total, K-available, plant dry weight, plant K concentration, K uptake, fresh and dry weight of shallot bulbs of Lembah Palu variety. Highest potassium uptake (11.07g) and maximum dry weight of shallot bulbs per clump was achieved at the rate of 60 t ha-1. Key Words: Potassium, shallot, and Titonia bokashi.